Genetic overlap between self-assessed intelligence, measured IQ and personality - Bratko, Denis; Chamorro-Premuzic, Tomas; Stumm, Sophie von; Butković, Ana; Vukasović, Tena (2011)
Recent studies have shown that self-assessed intelligence (SAI) is correlated with measured IQ and personality, and that both are significant predictors of SAI. In this study we investigated to which extent genetic and environmental influences contributing to SAI, measured IQ and personality are shared, and to which extent they explain their phenotypic relations. Sample included 83 MZ and 173 DZ twin pairs. For SAI participants had to give estimate of their overall intelligence, as well as for verbal/linguistic, logical-mathematical, musical, body-kinesthetic, spatial, interpersonal, intrapersonal, naturalist, spiritual and existential intelligence using normal distribution of intelligence scores. Estimate of overall intelligence (SAI-E) and first factor score for multiple intelligences (SAI-F) were used as measure of SAI. Psychometric intelligence was assessed by Croatian adaptation of subtest of General Aptitude Test Battery measuring verbal ability. Personality was measured with NEO-FFI. When SAI-E was used as a measure of SAI, significant genetic overlap was found with measured IQ and openness indicating that 63% and 82% of their phenotypic correlation is due to shared genetic influences. When SAI-F was used as measure of SAI, genetic overlap was found with neuroticism and openness indicating that their total phenotypic correlation is due to shared genetic influences.
Knjiga sažetaka nije tiskana, već je dostupna isključivo na službenoj internetskoj stranici: http://www.issid2011.com/program/papers_full.pdf
Projekt MZOS
ENG